2017
DOI: 10.3389/fpsyg.2016.02046
|View full text |Cite
|
Sign up to set email alerts
|

Triadic Interactions in Families of Adolescents with Anorexia Nervosa and Families of Adolescents with Internalizing Disorders

Abstract: The latest studies and practice guidelines for the treatment of adolescent patients with anorexia nervosa agree in pointing out the key role played by parents in determining the young patients’ therapeutic possibilities and outcomes. Still family functioning has usually been studied using only self-reported instruments. The aim of the present study is therefore to investigate the triadic interactions within the families of adolescents with anorexia nervosa using a semi-standardized observational tool based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 75 publications
4
31
0
Order By: Relevance
“…However, a dyadic peaceful interaction between one parent and the daughter might sometimes be interpreted as a sign of the apparent serenity of a symbiotic relationship, where the aggressiveness may be denied or cut off and cannot be used by the daughter to organize her adolescent individuation process (Balottin, Mannarini, Rossi, Rossi, & Balottin, 2017;Jeammet, 2010;Russell, Kopec-Schrader, Rey, & Beumont, 1992). This hypothesis is in line with the finding of a decreased quality of the interaction in the triadic phase, when families of daughters with anorexia were required to display a greater triangular coordination (Balottin, Mannarini, Mensi, et al, 2017). In line with these findings, this study showed that, differently from what happens in the dyadic phases, the adolescent's specific difficulties in the triadic interactions, as well as the impossibility to carve out a parental couple-specific relational space on the parents' part, appeared connected to the severity of the clinical presentation of adolescent anorexia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a dyadic peaceful interaction between one parent and the daughter might sometimes be interpreted as a sign of the apparent serenity of a symbiotic relationship, where the aggressiveness may be denied or cut off and cannot be used by the daughter to organize her adolescent individuation process (Balottin, Mannarini, Rossi, Rossi, & Balottin, 2017;Jeammet, 2010;Russell, Kopec-Schrader, Rey, & Beumont, 1992). This hypothesis is in line with the finding of a decreased quality of the interaction in the triadic phase, when families of daughters with anorexia were required to display a greater triangular coordination (Balottin, Mannarini, Mensi, et al, 2017). In line with these findings, this study showed that, differently from what happens in the dyadic phases, the adolescent's specific difficulties in the triadic interactions, as well as the impossibility to carve out a parental couple-specific relational space on the parents' part, appeared connected to the severity of the clinical presentation of adolescent anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…We can also suppose that these adolescents suffer from a less serious psychopathological condition, because from the beginning of the treatment, they showed better triadic interactive and relational abilities, which may be linked to a more positive perception of autonomy and separation, although sometimes conflictual, from the parents (Brusset, ; Jeammet, ; Russell et al, ). According to recent studies on family functioning and adolescent anorexia (Balottin, Mannarini, Mensi, et al, ; Wallis, Miskovic‐Wheatley, et al, ), a decline in the mother–daughter and father–daughter relationship quality may just reflect a physiological adolescent autonomy process. Accordingly, the main guidelines for the management of eating disorders (APA, ; Espie & Eisler, ; Hay et al, ; Herpertz‐Dahlmann et al, ; Lock et al, ; NICE, ), support family therapy as the first line treatment, especially in the case of less sever and younger patients with a recent onset of anorexia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of AN, findings from researchers using self‐report measurements of attachment report that patients with AN describe their fathers as highly critical, less caring, and more controlling (Orzolek‐Kronner, ). Furthermore, results indicate a paternal tendency to be emotionally absent, cold, and defensive in response to their daughter's illness (Ballotin, Mannarini, Mensi, Chiappedi, & Gatta, ). As a result, patients with AN might feel more alienated from their fathers (Gander et al, ; Horesh, Sommerfeld, Wolf, Zubery, & Zalsman, ; Orzolek‐Kronner, ), which consequently affects the quality of family interactions and the treatment outcome (Ballotin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results indicate a paternal tendency to be emotionally absent, cold, and defensive in response to their daughter's illness (Ballotin, Mannarini, Mensi, Chiappedi, & Gatta, 2017). As a result, patients with AN might feel more alienated from their fathers (Gander et al, 2015;Horesh, Sommerfeld, Wolf, Zubery, & Zalsman, 2015;Orzolek-Kronner, 2002), which consequently affects the quality of family interactions and the treatment outcome (Ballotin et al, 2017). A closer investigation of traumatic experiences and unresolved attachment status in fathers might help to gain a better understanding of underlying mechanisms that cause these defensive responses in fathers.…”
Section: Attachment and Childhood Traumamentioning
confidence: 99%